COMPETING IN PLATFORM ECOSYSTEMS: A STRATEGIC FRAMEWORK FOR COMPLEMENTOR FIRMS' MARKETING AND INNOVATION CHOICES - Darma Rahmat Suraja; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
The expansion of digital platform ecosystems has transformed business competition by creating interconnected environments where platform leaders and complementor firms collaboratively generate value. Complementor firms play a significant role in enhancing ecosystem attractiveness through innovation, customer engagement, and service diversification. However, increasing competition and dependence on platform governance create strategic challenges for complementors in balancing innovation and marketing strategies. This study aims to examine the strategic choices of complementor firms and propose a framework explaining how marketing and innovation capabilities influence competitiveness within platform ecosystems. Using a qualitative approach, the study explores strategic patterns adopted by complementors, including innovation-oriented, marketing-oriented, and hybrid strategies. The findings indicate that marketing strategies improve customer engagement and ecosystem visibility, while innovation strategies strengthen competitive differentiation and product sustainability. The study further highlights the influence of platform governance on complementor adaptability and performance. This research contributes to platform ecosystem literature by providing a strategic framework for complementor competitiveness in dynamic digital markets.